China’s Renewable Energy Innovation that Impact the World as Venture to Vanquish the Energy Crisis - Wicaksono, Daffa Adila; Mulya, Mutiara (Journal of International Relations on Energy Affairs, 2023)
The world is experiencing energy crisis today due to the Russian invasion in Ukraine that affect the global market as Russia cuts off its energy supply. Renewable energy is considered as a solution for the energy crisis since it’s sustainable and can replace the old energy sources. China as the energy innovator, believed to influence the world with its renewable energy innovation since China has become the world’s largest renewable energy producer that distributed its renewable energy. By following in China's footsteps in developing renewable energy, countries in the world have the potential to be independent and not depend on other countries for energy.